Psychobiological impact of speaking a second language in healthy young men - Fischer, Susanne; Ditzen, Beate (Stress, 2019)
The use of second languages is ubiquitous in modern societies. Despite many benefits, there is also evidence for this to cause or exacerbate stress (e.g. in the form of foreign language anxiety). The aim of the present study was to examine to which extent speaking a second language increases acute psychobiological stress in a social context. A total of N = 63 healthy Swiss males were randomly allocated to one of two conditions: completing the Trier Social Stress Test (TSST) in Swiss German (their first language) vs. standard German (perceived as a second language). Repeated measures of self-reported stress, anxiety, salivary cortisol, and heart rate were obtained. Participants speaking standard German showed significantly larger cortisol increases in response to the TSST when compared to those speaking Swiss German (F(1, 61) = 5.53, p = .022, eta2 = .083). The two groups did not differ in terms of self-reported stress and anxiety, nor in their heart rate response (all p > .216). This study provides initial evidence that speaking a second language in social contexts increases the cortisol stress response. Future research should explore the short- and long-term effects this may have in populations frequently using second languages (e.g. learners of a second language, migrants).
Gesehen am 03.07.2019